Bud source, asepsis and benzylaminopurine (BAP) effect on yacon (Polymnia sonchifolia) micropropagation - Mogor, G. [UNESP]; Mogor, A. F. [UNESP]; Lima, Giuseppina Pace Pereira [UNESP] (My University, 2004)
The yacon (Polymnia sonchifolia) is used largely for the high fructan content of its tubers; consequently, it is a good alternative for diabetics. One of the more important restricting factors of the commercial production of yacon is its susceptibility to nematode attack. This, as well as germplasm bank maintenance, justifies the importance of in vitro propagation of this species. In this way, our work aimed to verify the best asepsis method for yacon for the in vitro establishment from the rhizophore and the axillary buds of the aerial parts, and the effect of benzylaminopurine (BAP) addition to the culture medium. The number of contaminated cultures, the occurrence of phenolic oxidation and the occurrence of a vitreous aspect, showed differences with bud source, immersion time for asepsis, and BAP use. The results contribute to establishing a yacon micro propagation procedure.
Keywords: Clonal propagation; Cytokinin; Oxidation; Rhizophore; Tissue culture; Yacon